Agribusiness Opportunity for Rural Development in Nepal - Bhandari, Ramesh (Intellectual Journal of Academic Research, 2024)
The article explores the pivotal role of agribusiness in Nepal's economic landscape, particularly its potential for fostering rural development. It highlights the significant yet challenged contribution of agriculture to Nepal's GDP and employment. The objective is to analyze agribusiness's economic impact and its potential to drive rural development. The statement of the problem addresses issues such as inadequate infrastructure, limited market access, and insufficient financial resources that hinder agribusiness's effectiveness. Methodologically, the study utilizes secondary data, analyzing statistical data, scientific articles, and books to assess Nepal's agricultural sector's contribution to the economy. The discussion underscores the importance of transforming subsistence farming into commercial farming to enhance productivity and market integration, thereby promoting rural development. The conclusion emphasizes the need for targeted policies and investments to address these challenges and harness agribusiness's full potential for economic growth and rural development in Nepal. The diverse agro-climatic conditions in Nepal support various agricultural activities, providing a strong foundation for developing a vibrant agribusiness sector. By leveraging these opportunities and addressing challenges such as global competition and technological costs, Nepal can enhance its agribusiness sector, drive rural development, and boost overall economic growth.